2007
DOI: 10.1212/01.wnl.0000267430.95106.ff
|View full text |Cite
|
Sign up to set email alerts
|

Sixty hertz pallidal deep brain stimulation for primary torsion dystonia

Abstract: Stimulation of the internal globus pallidus at 60 Hz is safe and effective for treating medically refractory primary dystonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
97
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 21 publications
3
97
0
1
Order By: Relevance
“…This limitation may be overcome by rechargeable devices. A recent study found significant benefit using a much lower frequency of stimulation at 60 Hz [36]. The mean DBS parameters at the time of maximal improvement in our study were: mean amplitude 3.2 V, pulse width 170 μs and frequency 102 Hz, which were comparable to the previous studies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This limitation may be overcome by rechargeable devices. A recent study found significant benefit using a much lower frequency of stimulation at 60 Hz [36]. The mean DBS parameters at the time of maximal improvement in our study were: mean amplitude 3.2 V, pulse width 170 μs and frequency 102 Hz, which were comparable to the previous studies.…”
Section: Discussionsupporting
confidence: 87%
“…Two of our patients with primary dystonia had lower stimulation rates (60 and 80 Hz, respectively) and 1 with secondary dystonia had low stimulation rate (60 Hz). All of them showed good clinical response as noted by Alterman et al [36]. Adverse effects related to DBS are classified into three categories: surgical, hardware related, and stimulation related [37].…”
Section: Discussionmentioning
confidence: 88%
“…The therapeutic benefit of pallidal DBS has been widely established in the dystonic syndrome irrespective of primary, 1,[5][6][7]10,12,14,16,19,20,22,29 secondary, or heredodegenerative dystonia. 15,39,41 Some studies found the DYT1 mutation to be a prognostic factor of a successful outcome of pallidal DBS, [3][4][5]13,37,42 while others did not.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical results of pallidal DBS in pediatric patients (≤ 10 years of age) who underwent pallidal DBS are summarized in Table 1. As in adult cases, marked improvements of over 80% in dystonic symptoms, according to the Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) for movement, were documented in some early pediatric cases; 1,5,16,29,33 on the other hand, there also exist improvements below 30% on the BFMDRS, 26,32,46 suggesting that a careful evaluation is necessary before attempting surgical intervention in the brain of a patient who is too young. 26 To date, there have been few reports of dystonia recurrence, which may reflect a possible bias that poor outcomes were not published.…”
mentioning
confidence: 99%
“…11,21 Despite these seemingly positive outcomes, it appears that children with secondary dystonia respond less robustly to treatment in general, and to DBS in particular. 2 Clearly, the rarity of these disorders precludes the design of adequate trials, but it appears that the experiences of multiple institutions supports continued research into the application of DBS for secondary dystonia in medically refractory cases.…”
Section: Current Indications For Pediatric Dbsmentioning
confidence: 99%